The Promise of Automated Home-Cage Monitoring in Improving Translational Utility of Psychiatric Research in Rodents - Mingrone, Alfred; Kaffman, Ayal; Kaffman, Arie (Frontiers in Neuroscience, 2020)
Large number of promising preclinical psychiatric studies in rodents later fail in clinical trials, raising concerns about the efficacy of this approach to generate novel pharmacological interventions. In this mini-review we argue that over-reliance on behavioral tests that are brief and highly sensitive to external factors play a critical role in this failure and propose that automated home-cage monitoring offers several advantages that will increase the translational utility of preclinical psychiatric research in rodents. We describe three of the most commonly used approaches for automated home cage monitoring in rodents (e.g. operant wall systems, computerized visual systems, and automatic motion sensors) and review several commercially available systems that integrate the different approaches. Specific examples that demonstrate the advantages of automated home-cage monitoring over traditional tests of anxiety, depression, cognition, and addiction-like behaviors are highlighted. We conclude with recommendations on how to further expand this promising line of preclinical research.